2002
DOI: 10.1095/biolreprod66.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Postovulatory Aging of Oocytes Decreases Reproductive Fitness and Longevity of Offspring1

Abstract: We analyzed the long-term effects of postovulatory aging of mouse oocytes on reproductive fitness and longevity of offspring. Hybrid (C57BL/6JIco x CBA/JIco) parental generation (F0) females were artificially inseminated at 13 h (approximately 1 h postovulation) or 22 h (approximately 10 h postovulation) after GnRH injection. Reproductive fitness of first generation (F1) females was tested from the age of 28 wk until the end of their reproductive life. In males, the testing period ranged from the age of 2 yr u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 13 publications
1
57
0
1
Order By: Relevance
“…To study whether these phenomena are associated with abnormal DNA methylation in offspring, we assayed DNA methylation patterns of imprinted genes in oocytes from offspring that had been derived from postovulatory aged oocytes [49]. We found that postovulatory oocyte aging caused a decline in reproductive outcomes, being consistent with previous reports [47,48]. Nevertheless, our results showed that methylation patterns at DMRs of Peg3, Snrpn, Peg1 and H19 in oocytes from aged-oocyte offspring were basically normal, with only a small number of oocytes showing aberrant methylation in DMR of Peg3.…”
Section: Dna Methylationsupporting
confidence: 87%
See 1 more Smart Citation
“…To study whether these phenomena are associated with abnormal DNA methylation in offspring, we assayed DNA methylation patterns of imprinted genes in oocytes from offspring that had been derived from postovulatory aged oocytes [49]. We found that postovulatory oocyte aging caused a decline in reproductive outcomes, being consistent with previous reports [47,48]. Nevertheless, our results showed that methylation patterns at DMRs of Peg3, Snrpn, Peg1 and H19 in oocytes from aged-oocyte offspring were basically normal, with only a small number of oocytes showing aberrant methylation in DMR of Peg3.…”
Section: Dna Methylationsupporting
confidence: 87%
“…Previous studies have shown that postovulatory oocyte aging gives rise to offspring suffering from a series of defects including an increased number of growth-retarded pups, delayed development of the righting reflex, and higher spontaneous motor activity and emotionality, as well as decreased reproductive fitness and longevity of offspring [47,48]. To study whether these phenomena are associated with abnormal DNA methylation in offspring, we assayed DNA methylation patterns of imprinted genes in oocytes from offspring that had been derived from postovulatory aged oocytes [49].…”
Section: Dna Methylationmentioning
confidence: 99%
“…However, more recent research has demonstrated a significant decline in live birth rates and an elevated instance of abnormalities in offspring (Tarin et al 1999). Tarin et al (1999Tarin et al ( , 2002 demonstrated that offspring originating from in vivo aged oocytes exhibited growth retardation, delayed development, heightened emotional state, decreased reproductive fitness and importantly decreased longevity. Although the specific factors within the post-ovulatory aged oocyte that so prominently affect offspring integrity have not been determined, it has been hypothesized that these abnormalities may stem from the transference of a subpopulation of dysfunctional mitochondria (Tarin et al 2002).…”
Section: Abnormalities In Offspringmentioning
confidence: 99%
“…Tarin et al (1999Tarin et al ( , 2002 demonstrated that offspring originating from in vivo aged oocytes exhibited growth retardation, delayed development, heightened emotional state, decreased reproductive fitness and importantly decreased longevity. Although the specific factors within the post-ovulatory aged oocyte that so prominently affect offspring integrity have not been determined, it has been hypothesized that these abnormalities may stem from the transference of a subpopulation of dysfunctional mitochondria (Tarin et al 2002). Impaired mitochondrial function has indeed been linked with diseases such as schizophrenia (Whatley et al 1996), Alzheimer's disease (Hutchin & Cortopassi 1995, Budd & Nicholls 1998) and a decreased lifespan (Sont & Vandenbroucke 1993).…”
Section: Abnormalities In Offspringmentioning
confidence: 99%
“…Fertilization of postovulatory aged oocytes gives rise to mice suffering from nervous and emotional abnormalities (Tarin et al 1999) and decreased reproductive fitness and longevity (Tarin et al 2002). Humans and some animals potentially undertake sexual activity on any day of the estrous cycle, which may cause fertilization of aged ovulated oocytes.…”
Section: Introductionmentioning
confidence: 99%